Analisis Pola Konsumsi Diversifikasi Pangan dalam Meningkatkan Ketahanan Pangan Rumahtangga Petani Desa Saritani Kecamatan Wonosari Kabupaten Boalemo - Atiki, Nurul Lailah; Bakari, Yuliana; Hippy, Mohammad Zubair (Universitas Galuh, 2025)
Saritani Village, located in a remote area with limited distribution access, remains food-insecure despite the predominance of agriculture-based livelihoods. This study aims to examine household food consumption pattern and identify the key factors influencing food diversification among farming households in Saritani Vilage, Wonosari Sub-district, Boalemo Regency. A quantitative research design was employed, utilizing multiple linear regression analysis. Data werw collected through surveys, inetrviews, and structured qusetionnaires. Results indicate that the average daily energy adequacy (1,732 kcal/gram/day) remains below the recommended threshold. The education level of housewives demonstrated a statistically significant but negative effect on food diversification. Similarly, the number of household dependents had a negative impact. In contrast, household expenditure positively influenced diversification, while food availability, although positively correlated, did not exhibit a statistically significant effect. These findings highlight the need for strategic interventions to promote food diversification and improve food security in rural, agriculture-dependent communities such as Saritani Village.